Strategi Pembinaan Keagamaan Bagi Narapidana Muslim Di Lembaga Pemasyarakatan Kelas II B Sanana Kabupaten Kepulauan Sula - Pawah, Eka Diana (JUANGA: Jurnal Agama dan Ilmu Pengetahuan, 2021)
Tesis ini membahas tentang Strategi Pembinaan Keagamaan Bagi Narapidana Muslim Di Lembaga Pemasyarakatan Kelas II B Sanana Kabupaten Kepulauan Sula Provinsi Maluku Utara dengan tujuan untuk mengetahui strategi pembinaan keagamaan bagi narapidana muslim di Lembaga Pemasyarakatan dan untuk menganalisa efektifitas pembinaan keagamaan bagi narapidana muslim di Lembaga Pemasyarakatan. Sehingga Memberikan konstribusi pemikiran mengenai pembinaan keagamaan bagi narapidana muslim dan peningkatan kesadaran keagamaan narapidana dan petugas pembinaaan di Lembaga Pemasyarakatan Kelas II B Sanana. Penelitian dalam penulisan tesis ini adalah penelitian lapangan dengan menggunakan pendekatan kualitatif, dengan rancangan deskriptif dengan jumlah subjek penelitian sebanyak 9 (Sembilan) orang yang terdiri dari petugas pembinaan keagamaan, Petugas Lembaga Pemasyarakatan, dan Narapidana, Teknik pengumpulan data yang digunakan yaitu observasi, wawancara, dan dokumentasi. H Religious life is a fundamental right of every human being . The State also guarantees freedom of religion to all citizens . Whoever he is, whatever his status , required to practice their religion , including the inmate who is serving a sentence in prison . It is necessary to understand how religious building strategies for Muslim inmates in prison and how the effectiveness of religious construction of Muslim prisoners at the penitentiary . This study aims to determine the strategy for the construction of religious Muslim inmates in prison and to analyze the effectiveness of a religious building for Muslim inmates in prison . Up to Provide contribution to religious thought about the construction of Muslim prisoners and religious prisoners and awareness-raising officer in prison construction nationwide Class II B Sanana .The research in this thesis is a field research using qualitative approach with descriptive design with a number of research subjects as much as 9 ( nine ) members consisting of officers fostering religious , Prison officials and inmates , Data collection techniques used are observation , interview , and documentation .Results of this study concluded that the development strategy conducted in prisons Class II B Sanana need for additional personnel to conduct training because between inmates and officers less balanced development . While the effectiveness of religious guidance for Muslims prisoners in Penitentiary class II B Sanana although in practice there are still many shortcomings , but has led to a better direction . So that raises awareness in the hearts of inmates and can return to live peacefully in the midst of society . This was evidenced by the lack of recidivism figures in the Penitentiary Class II B Sanana